A description of the Stone space of Banach lattice C(K,E) - Zafer Ercan (Journal of Function Spaces and Applications)
We give a topological description of the Stone space of C(K,E), Banach lattices of continuous functions from a compact Hausdorff space K into a Banach lattice E.